2005
DOI: 10.1029/2005gl024027
|View full text |Cite
|
Sign up to set email alerts
|

X‐ray bursts produced by laboratory sparks in air

Abstract: X‐ray observations were made during fourteen 1.5 to 2.0 m high‐voltage discharges in air produced by a 1.5 MV Marx circuit. All 14 discharges generated x‐rays in the ∼30 to 150 keV range. The x‐rays, which arrived in discrete bursts, less than 0.5 microseconds in duration, occurred from both positive and negative polarity rod‐to‐plane discharges as well as from small, 5–10 cm series spark gaps within the Marx generator. The x‐ray bursts usually occurred when either the voltages across the gaps were the largest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
85
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(92 citation statements)
references
References 15 publications
6
85
1
Order By: Relevance
“…They were first observed in 1994 from the Compton Gamma‐ray Observatory satellite (Fishman et al, 1994) and later confirmed by other space‐based observations (Briggs et al, 2010; Marisaldi et al, 2010; Smith et al, 2005). X‐rays have also been observed at closer proximity to the source with sensors on the ground and on balloons (Dwyer, 2004; Mallick et al, 2012; Moore et al, 2001) and in high‐voltage laboratory discharge experiments of long sparks (Babich et al, 2015; Dwyer et al, 2005; Kochkin et al, 2014, 2016). The X‐ray and γ ‐ray are produced by high‐energy, runaway electrons through the bremsstrahlung process; however, the acceleration process of these electrons is still under debate.…”
Section: Introductionmentioning
confidence: 99%
“…They were first observed in 1994 from the Compton Gamma‐ray Observatory satellite (Fishman et al, 1994) and later confirmed by other space‐based observations (Briggs et al, 2010; Marisaldi et al, 2010; Smith et al, 2005). X‐rays have also been observed at closer proximity to the source with sensors on the ground and on balloons (Dwyer, 2004; Mallick et al, 2012; Moore et al, 2001) and in high‐voltage laboratory discharge experiments of long sparks (Babich et al, 2015; Dwyer et al, 2005; Kochkin et al, 2014, 2016). The X‐ray and γ ‐ray are produced by high‐energy, runaway electrons through the bremsstrahlung process; however, the acceleration process of these electrons is still under debate.…”
Section: Introductionmentioning
confidence: 99%
“…After the electron flux is computed, the radiated electric field due to the streamer current is calculated by means of equation (6). The spectrum is calculated with the obtained time domain electric field (z, ).…”
Section: Resultsmentioning
confidence: 99%
“…At ground, x-ray emissions are associated at the leader step phase [3][4][5]. These two discoveries promoted the mechanisms of X-ray radiation in laboratory sparks [6][7][8][9]. The investigations show that x-ray primary occur before the breakdown in fast voltage impulses.…”
Section: Introductionmentioning
confidence: 99%
“…Laboratory tests have shown that long sparks in air are accompanied by a rapid increase in the number of fast electrons with wide energy spectrum (1-300 keV) followed by X-ray bursts and strong flashes of γ photons up to a few MeV possibly related to the runaway breakdown (Gurevich et al, 1999a;Babich et al, 2004;Dwyer et al, 2005;Rahman et al, 2008;Milikh and Roussel-Dupré, 2010). However, these experiments cannot provide us with unambiguous evidence of the leading mechanism of the effect since the applied field was about 1.1 MV m −1 , which is smaller than that of conventional breakdown and greater than that of runaway breakdown.…”
Section: V Surkov and M Hayakawa: Underlying Mechanisms Of Transmentioning
confidence: 99%